A futures perspective of health, climate change and poverty in the United States. (August 2021) - Tonn, Bruce; Hawkins, Beth; Rose, Erin; Marincic, Michaela
Highlights: Trends assessments suggest that poverty and health will worsen in the U.S. Climate change will exacerbate these trends. Tens of millions of Americans may be displaced from their homes. Innovative suburban and rural settlements may become climate refuges. Changes in land use and affordable housing policies are required. Abstract: Trend assessments suggest that poverty and health will worsen in the United States in the coming decades and that climate change will exacerbate these trends. An aging society, lack of affordable housing, and automation threaten the economic sustainability of millions of households. Despair, drug abuse, and unhealthy lifestyles have led to the first decline in life spans in the U.S. during a non-war period. Extreme weather events caused by climate change can be anticipated to disrupt economic activities and destroy homes and infrastructure, pushing millions of more Americans into poverty. A warming climate threatens vulnerable individuals, such as elders, with heat stress, increasing levels of air pollution, and increasing risks from new tropical diseases entering the country. It is anticipated that climate change will force tens of millions of Americans from their homes, creating The Great Migration (TGM) scenario. The welfare of the migrants will depend on what types of human settlements they migrate to. Seven different types of settlements are depicted within the TGM scenario, such as Willow Pond settlements that represent radical redesigns of suburbs to make them sustainable and resilient to climate change. Numerous recommendations are provided to foster positive outcomes with respect to TGM, including having the U.S. formally designate that the right to safe and adequate housing is a human right.